Thai EFL Undergraduate Learners’ Needs for English for Specific Purposes at Present - Phothongsunan, Sureepong (International Journal of Multidisciplinary in Management and Tourism, 2022)
EFL (English as a Foreign Language) learners’ needs and interests have been a main focus in the teaching and learning of English in the present day, including the teaching of English for various purposes, be it all undergraduate or graduate levels. This research was conducted to explore ESP (English for Specific Purposes) language needs of a group of Thai EFL undergraduates studying in a university in Thailand. A close-ended questionnaire was employed to collect data. It was found that most students had a preference to study both ESP and EGP (English for General Purposes) elements in an ESP course with the ratio of 3 to 4 for ESP to EGP as both would complement reciprocally. The key concentration of ESP classes needed should be on improving English communication skills and deepening student knowledge of specific technical terms and expressions as well as necessary concepts in certain professional disciplines. Implications from the study draw EFL teachers to the need to value learners’ needs and to perform needs analyses before offering the ESP program or course.